KEBUTUHAN GURU, SISWA, MATERI AJAR, DAN STRATEGI DALAM PENGEMBANGAN PEMBELAJARAN MENULIS KREATIF KONTEKS MULTIKULTUR - Zulaeha, Ida (Lembaran Ilmu Kependidikan, 2008)
Model of teaching and learning integrate multicultur insight into Indonesia lesson study is means effective to be awake student in communicate at context multicultur society. Research method of use is R & D. Seek an excuse of need assessment, 84,5% the student experience misunderstanding when communicate with friends of different cultural; 77,9% they required fasilitator and subject matter for comprehend of cultural his friends. Teacher require project of subject matter and model of teaching and learning. Project of subject matter develop with into multicultur insight in language skill. Concept of project teaching and learning study develop include syllabus, lesson plan, subject matter, and assessment. This concept of project development teaching and learning model the have of tentative, require of experiment at research phase furthermore. Kata Kunci: pembelajaran menulis kreatif bahasa Indonesia, konteks multikultur, materi ajar, strategi pembelajaran